2010
DOI: 10.1186/1471-2180-10-188
|View full text |Cite
|
Sign up to set email alerts
|

A single sequence context cannot satisfy all non-AUG initiator codons in yeast†

Abstract: BackgroundPrevious studies in Saccharomyces cerevisiae showed that ALA1 (encoding alanyl-tRNA synthetase) and GRS1 (encoding glycyl-tRNA synthetase) respectively use ACG and TTG as their alternative translation initiator codons. To explore if any other non-ATG triplets can act as initiator codons in yeast, ALA1 was used as a reporter for screening.ResultsWe show herein that except for AAG and AGG, all triplets that differ from ATG by a single nucleotide were able to serve as initiator codons in ALA1. Among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 29 publications
3
22
0
Order By: Relevance
“…It is also unclear why other near-cognate triplets in an optimal context in the leader of GCN4 mRNA, and presumably many other genes, were not detectably translated in vivo (88). Results from a separate study suggested that nucleotides besides the critical Ϫ3 position significantly affect initiation from certain nearcognate triplets (30).…”
Section: Metmentioning
confidence: 97%
“…It is also unclear why other near-cognate triplets in an optimal context in the leader of GCN4 mRNA, and presumably many other genes, were not detectably translated in vivo (88). Results from a separate study suggested that nucleotides besides the critical Ϫ3 position significantly affect initiation from certain nearcognate triplets (30).…”
Section: Metmentioning
confidence: 97%
“…It has been observed through several studies has proved for example in yeast in 2010, that thought investigating different genes like ALA1 encodes alanyl-tRNA synthase and GRS1 encodes glycyltRNA synthase use ACG and TTG as their alternative translation start codon. It has been proved by [5] that except for AAG and AGG, all triplets that differ from ATG by a single nucleotide were able to serve as initiator codons in ALA1. It has been concluded that from these initiator codons, TTG, CTG, ACG, and ATT that had *50 % initiating activities compared to that of ATG, they indicated that the GTG, ATA, and ATC had *20 % initiating activities compared to that of ATG.…”
Section: Sequence Analysis and Phylogenetic Comparisons Within Mastermentioning
confidence: 99%
“…Unexpectedly, these non-AUG initiator codons showed different favoring actions toward different sequence backgrounds. Specifically, GTG was one of the most efficient non-ATG initiator codons [5,7].…”
Section: Sequence Analysis and Phylogenetic Comparisons Within Mastermentioning
confidence: 99%
“…Non-AUG initiator codons refer to triplets that differ from AUG by 1 nucleotide, such as GUG, UUG, AUU, and ACG (23). However, relatively few examples of non-AUG initiation have been found in lower eukaryotes.…”
mentioning
confidence: 99%
“…Although translation initiation from an AUG codon is not affected by its surrounding sequence in yeast (24)(25)(26), translation initiation from a non-AUG codon is greatly affected by its surrounding sequence. The best sequence context for a non-AUG initiator codon is AAA at its relative Ϫ3 to Ϫ1 positions (23,27), and a non-AUG initiator codon requires at least an A at its relative Ϫ3 position to be properly functional. A peculiar feature of ALA1 is that the gene uses AUG1 as the translation initiation codon of its cytoplasmic form while using two upstream consecutive ACG codons (ACG/ACG) as the translation initiation codons of its mitochondrial isoform (12).…”
mentioning
confidence: 99%